Memory and likeness of Fulbert Youlou (1947-1963) - Zéphirin Sah; Raymond Menga-Poaty (CV. Ridwan Publisher, 2023)
Under the colonial period, certain leaders of sub-Saharan Africa having received intellectual training gradually asserted themselves in the political arena. Among this elite, one of the emblematic figures is Abbé Fulbert Youlou, one of the fathers of the independence of the Congo between 1960 and 1963. He belongs to the Kongo ethnic group whose members were under French colonization, the head poster of the intellectual elite known as